A cross-linkable hole transport material having improved mobility through a semi-interpenetrating polymer network approach for solution-processed green PHOLEDs. Issue 29 (13th June 2018) - Park, So-Ra; Kang, Ji-Ho; Ahn, Dong A; Suh, Min Chul
Abstract : A novel cross-linkable hole transport material (HTM) was used to form a robust layer structure upon continuous wet processes such as spin coating or ink-jet printing. Abstract : A novel cross-linkable hole transport material (HTM) was used to form a robust layer structure upon continuous wet processes such as spin coating or ink-jet printing. The significantly reduced hole mobility of the cross-linked HTM (x-HTM ) was dramatically improved by a semi-interpenetrating polymer network (semi-IPN) approach for ideal charge balance. In other words, we obtained a synergistic effect from the blending of a linear hole transport polymer [TFB, poly(9, 9-dioctylfluorene- co-N -(4-butylphenyl)diphenylamine)] with a newx-HTM that realizes pretty low solubility in common organic solvents as well as significantly enhanced hole transport characteristics. As a result, it gave highly efficient solution-processed green phosphorescent organic light-emitting diodes (PHOLEDs) showing a pretty high current efficiency and external quantum efficiency of approximately 51.6 cd A −1 and 14.6% at the blending ratio of 20% (TFB). Particularly, the device lifetime was remarkably improved by a factor of 6.5 compared to the reference device which used an intrinsicx-HTM . To understand the reason for such outstanding improvement, we performed impedance spectroscopy (IS).